Theoretical studies of bioferroelectricity in DNA/RNA nucleobases and their base pairs / Yam See Chuan - Yam, See Chuan (2019)
We have performed computational molecular modelling to study the ferroelectric polarization switching and hysteresis loop behaviours of DNA/RNA nucleobases and their base pairs. All the nucleobases and base pairs - adenine (A), thymine (T), guanine (G), cytosine (C), uracil (U), guanine-cytosine (G-C), adenine-thymine (A-T) and adenine-uracil (A-U) are modelled. Our simulation indicated that all the nucleobases and base pairs exhibit switchable polarization through the application of the electric field. The shape of polarization (P) versus electric field (E) hysteresis loop is square, implying a typical ferroelectrics behaviour. We also found an interesting relationship between the minimum electric field required for polarization switching Ec and the ratio of the topological polar surface area (TPSA) to the total surface area (TSA) of a nucleobase and base pair. In particular, the Ec of a nucleobase and base pair are inversely proportional to the TPSA/TSA ratio. Furthermore, the total length of the base pair against electric field shows a nonlinear relationship. We believe that our findings may contribute to the fundamental understanding of the possible existence of bioferroelectricity in the biological system.